Profitabilitas Bank Islam di Dunia: Faktor Solvabilitas, Likuiditas dan Kecukupan Modal dengan Moderasi Ukuran Perusahaan - Lestari, Renita Diyana; Guntur Kusuma Wardana; Abdul Hakim Yahya (Al-Mashrafiyah (Jurnal Ekonomi, Keuangan dan Perbankan Syariah), 2025)
Banks can be said to be able to manage operations well when there is an increase in profit. This research goal is to investigate the effectt of solvency, liquidity, and capital adequacy on profitability, with firm size serving as a moderating variable. The research focuses on Islamic banks worldwide for the period 2019-2023. A quantitative approach using a causality method was employed. The study population is composed of 188 members of the Islamic Financial Services Board, and the sample was selected using purposive sampling, resulting in 19 Islamic banks. Data analysis was conducted using panel data regression, which blends cross-sectional and time series data. The findings show that, individually, solvency and capital adequacy significantly affect the profitability of Islamic banks globally, while liquidity does not. In contrast, when considered together, solvency, liquidity, and capital adequacy significantly influence profitability. Firm size moderates the effect of solvency on profitability, but does not moderate the effects of liquidity and capital adequacy on the profitability of Islamic banks worldwide. The implications of this research indicate that Islamic banks need to pay attention to solvency and capital adequacy to increase profitability. Liquidity that does not have a significant effect indicates the need for a more optimal management strategy. In addition, firm size can strengthen the influence of solvency on profitability, so that expansion and growth strategies are important for Islamic banks in increasing their competitiveness.